Hadis dan Hegemoni Paradigma Orientasi Fiqh - Rifqi Muhammad Fatkhi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2008)
This article proves its strength hegemony orientation of Fiqh in hadith region, even defeat the orientation of hadith itself and other orientation like orientation tasawuf. For the reason, this article also indicates that one of the forming factors of al-Kutub al-Sittah and its acceptance aspect, is more response of Fiqh interest rather than the codification of hadith. This at least shown by some primary factor that is orientation of Fiqh in hadith riwaya, forming of hadith school, and Fiqh main stream in hadith codification.